2020
DOI: 10.1039/d0cs00013b
|View full text |Cite
|
Sign up to set email alerts
|

Metallic nanostructures with low dimensionality for electrochemical water splitting

Abstract: The recent advances in 1D and 2D metallic nanostructures for electrochemical water splitting (HER and OER) are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
424
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(427 citation statements)
references
References 199 publications
3
424
0
Order By: Relevance
“…lectrocatalytic processes play a vital role in energy conversion and reducing the environmental pollution [1][2][3][4][5] . To improve the activity, selectivity, and stability of the catalytic reaction, it is necessary to develop high-performance advanced catalysts that can meet the needs of rapid development [6][7][8][9][10][11][12] . High-entropy alloys (HEAs) have attracted wide interest as catalytic materials in the past few years [13][14][15][16] .…”
mentioning
confidence: 99%
“…lectrocatalytic processes play a vital role in energy conversion and reducing the environmental pollution [1][2][3][4][5] . To improve the activity, selectivity, and stability of the catalytic reaction, it is necessary to develop high-performance advanced catalysts that can meet the needs of rapid development [6][7][8][9][10][11][12] . High-entropy alloys (HEAs) have attracted wide interest as catalytic materials in the past few years [13][14][15][16] .…”
mentioning
confidence: 99%
“…Recent studies have shown that loading active nanoparticles onto conductive substrates to form heterostructures could greatly enhance the stability and alter the local geometric and electronic structures at the interfaces due to the strong interaction between these two components. [14,15,[33][34][35][36] Among these conductive substrates, 2D porous carbon (2DPC) nanosheets demonstrated great potential with thicknesses of submicrometer/nanometer, interconnected pores, long-range conductivity and chemical stability. [37,38] Therefore, they could provide geometrical exposure, prevent deactivation, and maximize efficient contact with electrolytes during catalysis.…”
mentioning
confidence: 99%
“…[2,3] More importantly, the incompatibility and the sluggish kinetics for HER and OER can lead to inferior efficiency in a single watersplitting device. [4] Thus, designing an efficient bifunctional catalyst with high activity and stability is therefore needed to improve both the HER and OER performance under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the highest activity catalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is platinum (Pt) and iridium (Ir)/ruthenium (Ru) oxides, respectively, but the high price and scarcity greatly hinder their widespread adoption of industrial applications . More importantly, the incompatibility and the sluggish kinetics for HER and OER can lead to inferior efficiency in a single water‐splitting device . Thus, designing an efficient bifunctional catalyst with high activity and stability is therefore needed to improve both the HER and OER performance under the same conditions.…”
Section: Introductionmentioning
confidence: 99%